Carbon quantum dots/SnO2–Co3O4 composite for highly efficient electrochemical water oxidation. (October 2015) - Zhao, Shunyan; Li, Chuanxi; Liu, Juan; Liu, Naiyun; Qiao, Shi; Han, Yuzhi; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract: Nanocomposites based on transition metal oxides (Co3 O4, etc.) and carbon nanostructures with low-cost, high activity and good stability are promising catalysts toward electrochemical water oxidation, which is desirable but remains challenging. Here, we report the design and synthesis of nanocomposite based on carbon quantum dots (CQDs), SnO2 and Co3 O4 (CQDs/SnO2 –Co3 O4 ) as the electrocatalyst for highly efficient oxygen evolution reaction (OER). In alkaline media, the complex exhibited high electrocatalytic activity and long-term stability, which was better than either pristine Co3 O4 or SnO2 –Co3 O4 composite. Moreover, the CQDs/SnO2 –Co3 O4 with a molar ratio of Sn:Co at 1:3 revealed the highest catalytic activity toward OER among different molar ratios of CQDs/SnO2 –Co3 O4 composites. Experimental results indicated that the Co atoms were considered as the active centre, the nano-sized SnO2 enhanced electronic conductivity and the insoluble CQDs layer on the surface effectively protected the catalyst, thus the composite structure resulted in the excellent electrocatalytic activity and high stability.